Sharpening the relationship between cognitive complexity and moral choice - Çağlar, Mustafa Emre; Lufityanto, Galang (Current psychology (New Brunswick, N.J.), 2025)
Kant-based tradition suggests that complex moral reasoning improves moral choices, whereas intuitionists consider complex reasoning as an indicator of a desire to rationalize the immoral. The findings of this study support intuitionists, with one exception. In two studies conducted with a total of 195 subjects, two cognitive systems framing moral decisions came to the forefront. One is more complex than the other in terms of having multiple perspectives. It was observed that individuals who chose any of these systems and made relatively selfish decisions justified them in a more complex way. Among these selfish subjects, those who preferred the simpler system, supported their single perspectives with multiple reasons; whereas those who preferred the complex system, assumed useful perspectives to produce justifications that suited their interests. Complex reasoning contributes to the morality of the decision when it causes the decision maker to shift from the simple system to the complex one. However, according to our observations, such a shift during the decision period is not natural to human behavior, but it can still be triggered.